Food & technology - Glenise Perraton (John Wiley and Sons, 2005)
Food and Technology 1, 2nd edition" has been specifically written for the new VCE Food and Technology Study Design (implemented in 2006) for Units 1 and 2. The second book in this series covers Units 3 and 4. This series provides a comprehensive coverage of all of the key knowledge and key skills specified in the study design. The authors are experienced teachers and experts in the field of food and technology